PRONUNCIATION THROUGH TEAM ASSISTED INDIVIDUALIZATION TECHNIQUE - Baso, Farisha Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2014)
This research aimed to explain how the use of the Team Assisted Individualization Technique improve the students’ pronunciation dealing with the consonant sounds of Pronunciation and explain how the Team Assisted Individualization Technique improve the students’ pronunciation dealing with the vowel sound of pronunciation. This research method used a classroom action research which consisted of two cycleswith the subject was the studentsof SMK N 1 Minasate’ne Pangkep at class XI TKJ.1 in 2014/2015 academic year which consisted of 24 students, Pangkep regency and each cycle consisted of four meetings. The instruments of this research were observation sheet and pronunciation test or evaluation. The research findings indicated that Team Assisted Individualization Technique could improve the pronunciation of the students. It was proved by the pronunciation test of the students’ mean score in cycle 2 test result was (78,07) which improved from the cycle 1 mean score (68,35). It was highly improvement from diagnostic test (D – test) mean score (60,30). The Pronunciation test of the students achievement in cycle 2 indicated that it had met the researcher score target (70,00), and considered to be successful criteria in improving the pronunciationthrough Team Assisted Individualization Technique. Based on the findings above, the researcher made conclusion that by using Team Assisted Individualization Technique could improve the pronunciation of the students.